Tanggung Gugat Developer dan Penyedia KPR Terhadap Pembeli Perumahan atas Penggunaan Sertifikat Tanah Sebagai Agunan Bank (Studi Kasus Perumahan Violet Garden) - Nengah Erlina Wahyu Damayanti; Iswi Hariyani (Journal of Private and Economic Law, 2022)
Banks cannot provide mortgage facilities without collateral from developers because banks in providing credit facilities must apply collateral supply obligations. Explained in Article 8 of Law No. In the case of Violet Garden housing, it is known that the bank in providing mortgage facilities to residential buyers does not hold a certificate belonging to the buyer who is doing a mortgage where the debtor should submit the certificate to be used as collateral in the distribution of mortgages because the developer has guaranteed the certificate at another bank. So that for buyers who have paid off payments both in cash and mortgages can not make demands to process AJB in accordance with PPJB For the act, the form of developer liability on housing buyers for home certificates used to other banks to get the loan of funds is classified in the form of liability wanprestasi. Thus the developer must immediately redeem the home certificate or pay off the loan and compensate the losses incurred by the buyer, then in an effort to get the certificate of the aggrieved housing buyer can demand compensation with costs and interest by applying as a concurrent creditor to the curator by using ppjb evidence in accordance with Article 115 point 1 of Law No. 37 of 2004 on Bankruptcy and PKPU.